The development of national qualifications frameworks in Europe - (:unkn) unknown (Publications Office of the European Union, 2009)
"This report is the first in a series to be produced by Cedefop on a regular basis (twice a year) to provide an overview of European NQF developments. The main purpose of these regular reports is to support the exchange of experiences which already takes place between countries. Based on a comparative approach, our aim is to gradually deepen our analysis of national developments and provide more detailed information on solutions implemented. The picture presented in this report reflects the situation mid 2009 and is presented according to eight main headlines and themes: introductory remarks; rationale and main policy objectives; involvement of stakeholders; levels and level descriptors; use of learning outcomes; referencing to the EQF; lessons learned and the way forward; main sources of information. The conclusions drawn in this report are based on the interpretations of Cedefop and are not the responsibility of those generously providing the background information." (Hrsg., BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 1.3.3.3 Mobilität; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; I 2.2 Europa; EU-Bildungspolitik; Mobilität; Nationaler Qualifikationsrahmen; Durchlässigkeit im Bildungssystem; Lebenslanges Lernen; Europäische Union; Kroatien; Türkei; Island; Norwegen